Teachers' beliefs and practices regarding culture and intercultural communicative competence in Chinese teaching in the UK context - Ge, Ruilin (2015)
According to the British national language strategy (BNLS) (BDfES, 2002), foreign language (FL) teachers are expected to promote the learners’ acquisition of intercultural communicative competence (ICC) in class. As Chinese teaching has attracted attention and become popular in the UK currently, it is important for this study to explore Chinese teachers’ beliefs and practices with regard to culture and ICC in the context of TCFL.